Pengembangan Aplikasi Mobile untuk Mempermudah Pencarian Informasi Rute Angkutan Kota di Bandung - Priska Pricilia; Johanna Renny Octavia (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2017)
In the fast globalization era, people need good public transportation facilities to easily carry out their daily activities. However, public transportation such as angkutan kota mostly is not preferred compared to other modes of public transportation because it is difficult to acquire necessary information regarding angkutan kota routes in one area. This research aims to develop a mobile application to enhance the process of acquiring information of angkutan kota routes in Bandung. Eight potential users of the developed application were involved as participants in the research, from the identification of user needs through interviews and usability testing, the selection of design concept, to the evaluation of prototype. Based on the thirteen identified user needs, we developed two alternative design concepts from which we chose one best concept to be developed further into a prototype. The evaluation of the prototype through usability testing showed that the developed mobile application has good usability with 73% of efficiency measure, 90% of effectiveness measure, 78% of learnability measure and System Usability Score (SUS) of 71,25.